2011
DOI: 10.1111/j.1365-2605.2011.01147.x
|View full text |Cite
|
Sign up to set email alerts
|

Methylenetetrahydrofolate reductase C677T polymorphism and the risk of male infertility: a meta‐analysis

Abstract: Summary Several molecular epidemiological studies have been conducted to examine the association between MTHFR C677T polymorphism and male infertility susceptibility, but the results remain inconsistent. To derive a more precise estimation of the relationship, a meta‐analysis was performed. A total of 10 case–control studies, including 2275 cases and 1958 controls, were selected. Crude odds ratios (ORs) with 95% confidence intervals were used to assess the strength of association in the additive model, dominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
30
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 37 publications
7
30
1
Order By: Relevance
“…20 The potential associations between MTHFR genotype status and a number of medical complications have been evaluated using methodologies such as case-control, cohort, Mendelian randomization, and meta-analysis. A modest positive association has been found between the MTHFR "thermolabile" polymorphism and many different medical complications, including, but not limited to, thromboembolic disease (in non-North-American populations only), 21,22 stroke, [23][24][25][26][27] aneurysm, 28 peripheral artery disease, 29 migraine, 30 hypertension, 31,32 recurrent pregnancy loss, 33,34 male infertility, 35,36 risk for offspring with neural tube defects, 37,38 certain cancers, [39][40][41] neuropsychiatric disease, 42 and chemotherapy toxicity. 43,44 …”
mentioning
confidence: 99%
“…20 The potential associations between MTHFR genotype status and a number of medical complications have been evaluated using methodologies such as case-control, cohort, Mendelian randomization, and meta-analysis. A modest positive association has been found between the MTHFR "thermolabile" polymorphism and many different medical complications, including, but not limited to, thromboembolic disease (in non-North-American populations only), 21,22 stroke, [23][24][25][26][27] aneurysm, 28 peripheral artery disease, 29 migraine, 30 hypertension, 31,32 recurrent pregnancy loss, 33,34 male infertility, 35,36 risk for offspring with neural tube defects, 37,38 certain cancers, [39][40][41] neuropsychiatric disease, 42 and chemotherapy toxicity. 43,44 …”
mentioning
confidence: 99%
“…C677T, the most commonly studied MTHFR SNP, has been demonstrated to be associated with male infertility in certain populations but not in others (Bezold et al, 2001;Stuppia et al, 2003;A et al, 2007;Chellat et al, 2012;Vani et al, 2012). Several meta-analyses have suggested that C677T increases the risk of infertility (Tuttelmann et al, 2007;Gupta et al, 2011); however, a recent meta-analysis from Wu et al (2012) suggested that this SNP was only significantly associated with a susceptibility to male infertility in Asians, but not in Caucasians. Another study involving infertile and fertile and/or normospermic individuals of Korean ancestry found that the MTHFR C677T, Methionine Synthase Reductase (MTRR) A66G and methionine synthase (MS) A2756G genotypes were independently associated with male infertility (Lee et al, 2006).…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, a number of studies showed that supplementation with high-dose folic acid can significantly increase the total normal sperm count and sperm motility [53,54] , which influences the risk relationship between the MTHFR A1298C polymorphism and male infertility. Besides, the presence of other gene polymorphisms such as MTHFR C677T and MTRR A66G or congenital chromosomal abnormalities can also influence the association between the MTHFR A1298C polymorphism and male infertility [21,[55][56][57] . Male infertility is a multi-factorial condition that results from complex gene-environment, gene-nutrient and gene-gene interactions.…”
Section: Discussionmentioning
confidence: 99%